INTEGRUM BONUM ÎN CONCEPȚIA LUI AUGUSTIN. APLICAȚIE LA BINELE LIBERTĂȚII RELIGIOASE (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Integrum Bonum in the Concept of Augustin. Application to the Good of Religious FreedomIn the history of philosophy and theology, the good has been defined in various ways. As a fundamental right and democratic value, religious freedom is an absolutely necessary spiritual good for a civilized and free society. The present study summarizes Augustine’s conception of good. This synthesis will provide a general theoretical framework which can be applied to the specific good of religious freedom. Augustine’s thought, who defines good in connection with the concepts of nature, form, measure and order can make a useful contribution to the debates on religious freedom at both the political and ecclesial levels. The study concludes with a few reflections on religious freedom viewed from the perspective of the four Augustinian criteria.